Phytochemicals and Antidiabetic, Antioxidant and Anti-inflammatory Activities of Ethanol Flower Extract of Syzygium aromaticum (L.) Merr. & Perry (Myrtaceae) - Buddhakala, Nopparat; Yongkhamcha, Butsara; Rattanaloeadnusorn, Sukhan; Talubmook, Chusri (Trends in Sciences, 2022)
Syzygium aromaticum (L.) Merr. & Perry is a spice that has been used traditionally for centuries to preserve food and treat for a number of ailments. This research was carried out to analyze phytochemicals and to determine antidiabetic, antioxidant and anti-inflammatory activities of 95 % ethanol flower extract from S. aromaticum (FESA). The GC-MS analysis demonstrated the presence of 17 bioactive compounds in FESA, with eugenol (56.17 %) the most active compound. Antidiabetic activity study revealed that the inhibitory activity of the FESA against α-glucosidase enzyme was stronger than the activity of Acarbose, an antidiabetic drug. In addition, the FESA exhibited potent antioxidant activity by inhibiting 2, 2- diphenyl-1-picrylhydrazylhydrate (DPPH) free radicals higher than butylated hydroxyltoluene (BHT), a synthetic antioxidant. Furthermore, the FESA potentially inhibited the nitric oxide (NO) production in lipopolysaccharide (LPS)-induced RAW 264.7 cells but less effective than Diclofenac, a non-steroidal anti-inflammatory drug. The activities of FESA are partly due to the presence of active compounds. The results obtained confirm the antidiabetic, antioxidant and anti-inflammatory properties, and the traditional used of S. aromaticum for the treatment of diabetes and oxidative and inflammatory-related diseases. HIGHLIGHTS The most predominant bioactive compound in FESA is eugenol (56.17 %), analyzed by GC-MS FESA inhibits α-glucosidase activity significantly higher than acarbose, an antidiabetic drug. The FESA is therefore helpful to delay or possibly prevent the development of the diabetic complication The FESA exhibits DPPH radical scavenging activity is more potent than BHT, an antioxidant compound The FESA can provide a novel natural anti- inflammatory agent resource, as evidenced by the inhibitory effect of FESA on nitric oxide (NO) production GRAPHICAL ABSTRACT